Legal Politics of Land Dispute Settlement Post The Implementation of The Work Copyright Law in Realizing Security and Justice of Land Rights in Indonesia - Purwanto, Edi; Helmi, Helmi (Jurnal Hukum dan Keadilan, 2024)
The enactment of Law No. 11/2020 on Job Creation has drastically changed the legal policy on land rights, for example, building use rights and use rights provide rights not only to land on the surface of the earth but are now extended to above-ground and underground spaces. Another legal issue is the term of the right which is set at once up to 50 years for building use rights and 60 years for business use rights and still has the right to extend up to 30 years for building use rights or 35 years for business use rights. This research is a normative juridical research. This research aims to analyze the impact of changes in land rights legal policy caused by the Job Creation Law, as well as examine solutions that can be applied to solve the problem of agrarian law anomalies in Indonesia. As an implication, Indonesia currently has two laws that both regulate land rights, namely the Basic Agrarian Law and the Job Creation Law. This makes Indonesia's agrarian law an anomaly. The best solution to resolve this anomaly in land rights law is to not continue legal remaking Law Number 11 of 2020 or to reinterpret the norms.